Optimization of Ganciclovir-Loaded Nanoparticles for Ocular Delivery by Utilizing Box-Behnken Design - Verma, Shalu; Juyal, Divya (Indian Journal of Pharmaceutical Education and Research)
Aim: The study aimed to optimize Ganciclovir-loaded nanoparticles for ocular delivery by evaluating the relationship between experimental data and Design factors. Materials and Methods: The nanoparticles were developed using the ionic gelation method. A 3-level, 3-factor Box-Behnken Design (BBD) was used for the optimisation process. Selecting the concentrations of chitosan, Sodium Tripolyphosphate (STPP) and sonication time as the independent variables. Entrapment efficiency, Drug release and Drug loading were chosen as dependent variables. The dependent and independent variables were related using response surface plots and the obtained polynomial equations. Results: The entrapment efficiency, Cumulative drug release and drug loading of the optimised Ganciclovir-loaded Chitosan Nanoparticles (GCV-CS-NPs) were found to be 91.93%, 92.27% and 17.68%, respectively. Excellent correlation between the dependent and independent response variables demonstrated the rationality of the optimised GCV-CS-NPS. Conclusion: The GCV release from GCV-CS-NPS exhibited a biphasic pattern, with a 2-hr rapid release after a 12-hr sustained release. Following the Peppas model, the in vitro release of the resulting ganciclovir-loaded nanoparticles demonstrated sustained release.
Keywords: Nanoparticles; Box-Behnken design; Ganciclovir; Ocular delivery; Ionic gelation